2010
DOI: 10.1007/s10228-010-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

Description and innervation of the lateral line system in two gobioids, Odontobutis obscura and Pterogobius elapoides (Teleostei: Perciformes)

Abstract: Components of the lateral line system and their innervation were studied in Odontobutis obscura (Odontobutidae) and Pterogobius elapoides (Gobiidae), which are benthic and pelagic species, respectively. Innervation of the superficial neuromasts constituting the trunk lateral line system by way of three continuous longitudinal series (dorsal, middle, and ventral series: ld, lm, and lv series, respectively) became apparent for the first time. Innervation patterns indicated that the ld and lv series represented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Furthermore, Sanzo (1911) reported similarly developed rows on the entire trunk in Deltentosteus quadrimaculatus (see below). Primitively in gobioids, the mid-lateral series is consistently present along the lateral surface of the trunk, with some additional rows comprising the dorsolateral and ventrolateral series (Shibukawa et al 2001;Asaoka et al 2011). Therefore, the condition in G. olivaceus is apparently a specialization, In G. olivaceus, the lateral ramus detached a number of branches, each comprising the equally developed dorsal and ventral ramules, the first instance of such a branching pattern in the Gobioidei.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, Sanzo (1911) reported similarly developed rows on the entire trunk in Deltentosteus quadrimaculatus (see below). Primitively in gobioids, the mid-lateral series is consistently present along the lateral surface of the trunk, with some additional rows comprising the dorsolateral and ventrolateral series (Shibukawa et al 2001;Asaoka et al 2011). Therefore, the condition in G. olivaceus is apparently a specialization, In G. olivaceus, the lateral ramus detached a number of branches, each comprising the equally developed dorsal and ventral ramules, the first instance of such a branching pattern in the Gobioidei.…”
Section: Discussionmentioning
confidence: 94%
“…In Glossogobius olivaceus, five longitudinal rows [LA3 and LA4 of Hoese (1983) as c] are developed on the suborbital region, rows a, a 1 and c, and b and d being innervated by the buccal and mandibular rami, respectively, as in other gobioids, including the primitive species Odontobutis obscura, as far as is known (Wongrat and Miller 1991;Ahnelt and Bohacek 2004;Asaoka et al 2011). Regarding neuromast orientation, the LA (a, a 1 and c) and LT rows (b and d) are consistent with the above innervation, previous studies (e.g., Hoese 1983;Hoese and Lubbock 2000;Hoese and Reader 2001;Hoese and Larson 2010) having suggested that such consistency is common in gobioids, although more extensive taxonomic sampling is needed for confirmation.…”
Section: Discussionmentioning
confidence: 98%
“…No superficial neuromasts were identified in histological sections of X. mucosus , but this does not necessarily mean they are missing in the genus. Superficial neuromasts typically are smaller and more numerous than canal neuromasts (Münz, ; Wonsettler and Webb, ) and can be distributed in rows, clusters, and other patterns that are often species‐specific (Asaoka et al, ; Nakae et al, ; Schmitz et al, ). It is possible that superficial neuromasts are present in Xiphister but are small and were overlooked or are distributed in areas that were not sectioned.…”
Section: Discussionmentioning
confidence: 99%
“…2b) and description of nerves were based on 13 specimens, because not all nerves could be traced in few specimens. The terminology generally follows Asaoka et al (2011) for neuroanatomy.…”
Section: Methodsmentioning
confidence: 99%